Neuronal Mechanisms of Cortical Alpha Oscillations in Awake-Behaving Macaques - Bollimunta, Anil (Society for Neuroscience, 2008)
Field potential oscillations at ∼10 Hz (alpha rhythm) are widely noted in the visual cortices, but their physiological mechanisms and significance are poorly understood. In vitro studies have implicated pyramidal neurons in both infragranular and supragranular layers as pacemakers. The generality of these observations for the intact brain in the behaving subject is unknown. We analyzed laminar profiles of spontaneous local field potentials and multiunit activity (MUA) recorded with linear array multielectrodes from visual areas V2, V4, and inferotemporal (IT) cortex of two macaque monkeys during performance of a sensory discrimination task. Current source density (CSD) analysis was combined with CSD–MUA coherence to identify intracortical alpha current generators and their potential for alpha pacemaking. The role of each alpha current generator was further delineated by Granger causality analyses. In V2 and V4, alpha current generators were found in all layers, with the infragranular generator acting as primary local pacemaking generator. In contrast, in IT, alpha current generators were found only in supragranular and infragranular layers, with the supragranular generator acting as primary local pacemaking generator. The amplitude of alpha activity in V2 and V4 was negatively correlated with behavioral performance, whereas the opposite was true in IT. The alpha rhythm in IT thus appears to differ from that in the lower-order cortices, both in terms of its underlying physiological mechanism and its behavioral correlates. This work may help to reconcile some of the diverse findings and conclusions on the functional significance of alpha band oscillations in the visual system.